Studying the Three-Body Problem in the Effective Quantum Field Theory by using the Monte Carlo Method (Latakia University Journal -Basic Sciences Series, 2019)
This research is concerned with Efimov states of helium trimer 4He3; these states have universal characteristics displaying the interaction of three bodies at low energy, where the scattering length is greater than the range of interaction. The mathematical theory used in this study is the effective quantum field theory, which physically says that we do not need to know the physics of high energy  in order to study low energy physics. This theory enables us to get rid of the infinites by introducing the renormalization function. The numerical solution to integral equations has been carried out by using the Monte Carlo method.